Enhancing Public Service Performance through Motivation, Environment, and Discipline: Meningkatkan Kinerja Pelayanan Publik melalui Motivasi, Lingkungan, dan Disiplin - Faizi, Ahmad Nur; Sumartik; Oetarjo, Mas (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates how motivation, work environment, and work discipline influence the performance of Integrated Referral and Service System (SLRT) officers at the Social Affairs Office of Sidoarjo Regency. Using a quantitative approach with a Likert scale questionnaire administered to 85 SLRT officers, data were analyzed through multiple linear regression in SPSS 25. The results reveal that motivation, work environment, and work discipline significantly impact employee performance. Specifically, higher levels of motivation, supportive work environments, and strong work discipline correlate positively with enhanced performance among SLRT officers. These findings highlight the importance of fostering motivational factors, improving work environments, and maintaining effective work discipline to optimize service delivery and organizational effectiveness within public service sectors. Highlight: Employee motivation significantly impacts public service performance outcomes. A conducive work environment fosters higher productivity and job satisfaction. Discipline ensures adherence to standards and enhances organizational effectiveness. Keywords: Public service, employee performance, motivation, work environment, discipline